The spectrum of bacteria and mechanisms of resistance identified from the casualties treated in the Israeli field hospital after the earthquake in Nepal, 2015: A retrospective analysis. Issue 37 (September 2020) - Lachish, Tamar; Halperin, Tami; Snitser, Olga; Kashat, Livnat; Merin, Ofer; Bader, Tarif; Rokney, Assaf; Schwartz, Eli; Assous, Marc Victor
Abstract: Background: On the April 25, 2015, a 7.8 magnitude earthquake struck Nepal. Soon-after, the Israel Defense Force (IDF) dispatched a tertiary field-hospital to Kathmandu. The field-hospital was equipped with a clinical laboratory with microbiology capabilities. Limited data exists regarding the spectrum of bacteria isolated from earthquake casualties. We aimed to identify the spectrum of bacteria and their mechanisms of resistance in-order to allow preparedness of antibiotic treatment protocols for future disaster scenarios. Methods: – The field-laboratory phenotypically processed cultures from sterile and non-sterile sites as needed clinically. Later-on, the isolates were brought to Israel for quality control, definite identification and molecular characterization including mechanisms of resistance. Results: A total of 82 clinical pathogens were isolated from 56 patients; 68% of them were Gram negative bacilli. The most common isolates were Enterobacteriaceae (55%) −36% carried bla -NDM and 33% produced Extended-spectrum beta-lactamase (ESBL), mostly bla CTX-M-15 . Enterococcus spp were the main Gram positive bacteria isolated (22 isolates), yet, none were vancomycin resistant. The overall level of resistance was 27% MDR and 23% extensively drug resistant (XDR) bacteria. Conclusions: – Gram negative bacteria were the predominant organism cultured from the casualties, of them 77% were MDR or XDR. NDM was the most common resistance mechanism. The Antibiotic inventory of a field-hospital should be set to cover a wide and unexpected spectrum of bacteria, including resistant organisms. This report adds important information to the scarce reports of bacterial resistance in Nepal.